Management of Zakat at BAZNAS Regency Sidrap During COVID-19’s Pandemic - Wahyu, A. Rio Makkulau; Anwar, Wirani Aisiyah (Jurnal Iqtisaduna, 2020)
Zakat is an obligation for every Muslim who can purify his soul to zakat Fitrah and purify his property for Zakat Maal. Zakat must be managed properly so that the distribution of the property can run effectively and targeted to the Mustahik in the moment of the current Covid-19 pandemic. Baznas has made renewal in zakat management both in terms of collecting, distributing, and utilization of zakat funds. For example, in the case of fundraising Zakat is done by a digital system. The purpose of this research is to explain the management of Zakat done by the Baznas Sidrap Regency in maximizing the distribution of the accumulated zakat funds. The study was conducted using a combination of library and field research using a qualitative method with descriptive analysis. The research location was at Sidrap District. The results showed that zakat funds can be utilized to the fullest extent possible for the welfare of the Mustahik both consumptive and productive. In distributing the fund zakat Baznas Sidrap Regency has channeled the funds amounting to Rp.1,2 billion since the period of Covid-19 pandemic with the main channeling of zakat funds in remote areas that have been affected by Covid-19 pandemic, in the form of food aid for the consumptive.